Induced and Evoked Properties of Vibrotactile Adaptation in the Primary Somatosensory Cortex - Nicolaas A. J. Puts; Richard A. E. Edden; Suresh Muthukumaraswamy; Krish D. Singh; David J. McGonigle (Neural Plasticity)
Prolonged exposure to afferent stimulation (“adaptation”) can cause profound short-term changes in the responsiveness of cortical sensory neurons. While several models have been proposed that link adaptation to single-neuron dynamics, including GABAergic inhibition, the process is currently imperfectly understood at the whole-brain level in humans. Here, we used magnetoencephalography (MEG) to examine the neurophysiological correlates of adaptation within SI in humans. In one condition, a 25 Hz adapting stimulus (5 s) was followed by a 1 s 25 Hz probe (“same”), and in a second condition, the adapting stimulus was followed by a 1 s 180 Hz probe (“different”). We hypothesized that changes in the mu-beta activity band (reflecting GABAergic processing) would be modulated differently between the “same” and “different” probe stimuli. We show that the primary somatosensory (SI) mu-beta response to the “same” probe is significantly reduced (p=0.014) compared to the adapting stimulus, whereas the mu-beta response to the “different” probe is not (p=n.s.). This reduction may reflect sharpening of the spatiotemporal pattern of activity after adaptation. The stimulus onset mu-beta response did not differ between a 25 Hz adapting stimulus and a 180 Hz probe, suggesting that the mu-beta response is independent of stimulus frequency. Furthermore, we show a sustained evoked and induced desynchronization for the duration of the adapting stimulus, consistent with invasive studies. Our findings are important in understanding the neurophysiology underlying short-term and stimulus-induced plasticity in the human brain and shows that the brain response to tactile stimulation is altered after only brief stimulation.